Env-Specific Antibodies in Chronic Infection versus in Vaccination - Soldemo, Martina; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2017)
Antibodies are central in vaccine-mediated protection. For HIV-1, a pathogen that displays extreme antigenic variability, B cell responses against conserved determinants of the envelope glycoproteins (Env) are likely required to achieve broadly protective vaccine-induced responses. To understand antibodies in chronic infection, where broad serum neutralizing activity is observed in a subset of individuals, monoclonal antibodies mediating this activity have been isolated. Studies of their maturation pathways reveal that years of co-evolution between the virus and the adaptive immune response is required for such responses to arise. Further, they do so in subjects who display alterations of their B cell subsets caused by the chronic infection, conditions that are distinctly different from those in healthy hosts. So far, broadly neutralizing antibody responses were not induced by vaccination in primates or small animals with natural B cell repertoires. An increased focus on the development vaccine-induced responses in healthy subjects is therefore needed to delineate how the immune system recognizes different forms of HIV-1 Env and to optimize approaches to stimulate antibody responses against relevant neutralizing antibody epitopes. In this review, we describe aspects of Env-directed antibody responses that differ between chronic HIV-1 infection and subunit vaccination for an improved appreciation of these differences; and we highlight the need for an improved understanding of vaccine-induced B cell responses to complex glycoproteins such as Env in healthy subjects.